Absenteeism and its implications for nursing care in emergency services - Ione Carvalho Pinto; Brisa Polyana Gonçalves Figueira; Denise Ferro; Fabiana Costa Machado Zacharias; Mariana Figueiredo Souza Gomide; Ricardo Alexandre Arcêncio (Universidade Federal de Goias, 2017)
The aim of this study was to identify the frequency of absenteeism among nursing teams and its determinants in healthcare emergency services. A cross-sectional study was carried out by means of secondary data from records of a coordination of human resources. Occurrences with 208 nursing professionals were identified. Univariate analysis was carried out with frequency calculation of the variables age, gender, professional category, workplace, and days and reasons for absenteeism. Fisher's exact test was applied, fixing the error type I in 5%. The mean age of the participants was 47.2 years, with a prevalence of the female gender (79.8%). A total of 5,778 occurrences of absenteeism were found (mean of 28 per professional), and illness was the main determinant for absenteeism (2,671 occurrences; 46.2%). There was a prevalence of short-term absenteeism (3,020 occurrences; 52.3%). The findings observed in emergency services were similar, with a potential impact on planning, workforce, and quality of care.